THE ROLE OF TEACHER QUESTIONING IN DEVELOPING CRITICAL THINKING SKILLS AS A WAY TO INDEPENDENT LEARNING - Zakirova, Zulkhumor (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
This article explores how teachers' questioning methods impact foreign language learning. It analyzes question types (low-order to high-order) and their role in developing critical thinking. By asking effective questions, teachers can empower students to analyze information, solve problems, which opens the way for the learners to become independent learners.